2021
DOI: 10.1007/978-3-030-72699-7_38
|View full text |Cite
|
Sign up to set email alerts
|

Towards Feature-Based Performance Regression Using Trajectory Data

Abstract: Black-box optimization is a very active area of research, with many new algorithms being developed every year. This variety is needed, on the one hand, since different algorithms are most suitable for different types of optimization problems. But the variety also poses a meta-problem: which algorithm to choose for a given problem at hand? Past research has shown that per-instance algorithm selection based on exploratory landscape analysis (ELA) can be an efficient mean to tackle this meta-problem. Existing app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…As in [4,7,39], we did not perform feature selection because it deteriorated the performance of a classifier in our preliminary experiment. A similar observation was reported in [14]. This may be due to a leave-one-problem-out cross-validation (LOPO-CV) [7,16] (see the next section), where the prediction model is validated on an unseen function.…”
Section: Feature Setssupporting
confidence: 68%
“…As in [4,7,39], we did not perform feature selection because it deteriorated the performance of a classifier in our preliminary experiment. A similar observation was reported in [14]. This may be due to a leave-one-problem-out cross-validation (LOPO-CV) [7,16] (see the next section), where the prediction model is validated on an unseen function.…”
Section: Feature Setssupporting
confidence: 68%
“…Previous studies have already shown that models trained to predict the target precision reached by an algorithm or its logarithmic value perform differently [8,9]. There are problem instances for which the model trained to predict the target precision works well, however there are also problem instances for which the model trained to predict the logarithmic value of the target precision works better.…”
Section: Automated Algorithm Performance Predictionmentioning
confidence: 99%
“…Finally, in order to predict the performance of the algorithm on a new problem instance, a supervised ML method is trained using the landscape data as input data and the performance data as a target data. In recent studies, this is done by learning a single ML model using a set of ELA features that works well across all problem instances [8,9,12]. All these studies used classical feature selection methods to select the ELA features that should improve the performance of the ML model.…”
Section: Introductionmentioning
confidence: 99%
“…In [14], trajectory-based ELA regression models have been developed to predict the CMA-ES target precision obtained after a fixed number function evaluations. It has been shown that classical feature selection techniques applied on the ELA features in combination with random forest with no hyperparameter tuning did not lead to better performance results.…”
Section: Related Workmentioning
confidence: 99%
“…One issue in training those models is the selection of the ELA features that will be used to describe the problems. Some of the studies used the cheap ELA features, and some of them select a subset of the previously mentioned features using classical ML feature selection techniques [9], [14], [15]. The presented results showed that the selection of the ELA features portfolio influences the end performance prediction, but the impact of each feature to the end prediction result is still treated in a black-box manner.…”
Section: Introductionmentioning
confidence: 99%